Trust and distrust in a foreign-owned enterprise in China : an exploratory case study - Dew, Teck Chuan (2008)
This study aims to provide a more thorough understanding of trust, distrust and control, as well as practical insights for foreign managers operating in a wholly foreign-owned enterprise in China.